Health policy in emerging economies: Innovations and challenges - Michael MacLennan; Pedro Lara de Arruda; Jeni Vaitsman (International Policy Centre for Inclusive Growth (IPC-IG), 2016)
Over the last decade, the global health agenda has converged around proposals for the construction of policies and interventions towards greater equity. Despite the great diversity in their historical and institutional contexts, developing countries face similar health care challenges, including inequity regarding access to services and to quality medicines, the prevention and control of communicable and non-communicable diseases, and the strengthening of capacities in scientific and technological development. [...]
Keywords: 330; health policy; emerging economies; innovations; challenges